The Role of Underwriter-Investor Relationships in the IPO Process - Binay, Murat M.; Gatchev, Vladimir A.; Pirinsky, Christo A. (Journal of Financial and Quantitative Analysis, 2007)
Abstract We find that in allocating initial public offerings (IPOs), underwriters favor institutions they have previously worked with. Regular investors benefit more than casual investors in IPOs through greater participation in underpriced issues. Relationship participation is more important in the distribution of IPOs with stronger demand, IPOs of less liquid firms, and deals by less reputable underwriters. Overall, our results are consistent with book-building theories of IPOs. Interestingly, for 1999–2000 we find that regular investors receive even more underpriced IPOs relative to previous years while we do not find evidence that they provide additional services in IPOs.